PROSES MANUSIA DIHADIRKAN DAN AKHIRNYA LENYAP DALAM KETERBATASAN BAHASA - Ulfa, Ruzqiyah (Jurnal Nomosleca, 2017)
Foucault opens this book with a direct introduction to the concept of heterotopia. The term heterotopia is a neologism that Foucault deemed so frightening, for he "secretly destroys the language, for they allow it to give names on this and that, for they destroy and confound the common names, for they destroy the 'syntax' Furthermore". In the first chapter, Foucault made an introduction to what he would describe in depth in his book. He explained technically about the sign system of the Stoic period. Keywords: Language, Power and ScienceDOI : https://doi.org/10.26905/nomosleca.v3i1.1487